The impact of perception bias for cardiovascular disease risk on physical activity and dietary habits - Zhiting Guo; Yujia Fu; Xuyang Wang; Aline Aparecida Monroe; Yuping Zhang; Jingfen Jin; Meifen Chen (Elsevier, 2024)
Objective: Cardiovascular disease (CVD) remains a significant public health challenge in China. Accurate perception of individual CVD risk is crucial for timely intervention and preventive strategies. This study aimed to determine the alignment between CVD risk perception levels and objectively calculated CVD risk levels, then investigate the disparity in physical activity and healthy diet habits among distinct CVD risk perception categories. Methods: From March to August 2022, a cross-sectional survey was conducted in Zhejiang Province using convenience sampling. Participants aged between 20 and 80 years, without prior diagnosis of CVD were included. CVD risk perception was evaluated with the Chinese version of the Attitude and Beliefs about Cardiovascular Disease Risk Perception Questionnaire, while objective CVD risk was assessed through the Prediction for Atherosclerotic Cardiovascular Disease Risk (China-PAR) model. Participants' demographic information, self-reported physical activity, and healthy diet score were also collected. Results: A total of 739 participants were included in the final analysis. Less than a third of participants (29.2%) accurately perceived their CVD risk, while 64.5% over-perceived it and 6.2% under-perceived it. Notably, half of the individuals (50.0%) with high CVD risk under-perceived their actual risk. Compared to the accurate perception group, individuals aged 60-80 years old (OR = 6.569), currently drinking (OR = 3.059), and with hypertension (OR = 2.352) were more likely to under-perceive their CVD risk. Meanwhile, participants aged 40-<60 years old (OR = 2.462) and employed (OR = 2.352) were more likely to over-perceive their risk. The proportion of individuals engaging in physical activity was lowest in the under-perception group, although the difference among the three groups was not statistically significant (χ2 = 2.556, P = 0.278). In addition, the proportion of individuals practicing healthy diet habits was also lowest in the under-perception group, and a significant statistical difference was observed among the three groups (χ2 = 10.310, P = 0.006). Conclusion: Only a small proportion of participants accurately perceived their CVD risk, especially among those with high actual CVD risk. Individuals in the under-perceived CVD risk group exhibited the lowest rates of physical activity engagement and healthy diet adherence. Healthcare professionals should prioritize implementing personalized CVD risk communication strategies tailored to specific subgroups to enhance the accuracy of risk perception.